2022
DOI: 10.2147/ijgm.s346058
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Four-Gene Signature for Determining the Prognosis of Papillary Thyroid Carcinoma by Integrated Bioinformatics Analysis

Abstract: Purpose Although well-differentiated papillary thyroid carcinoma (PTC) has an indolent nature and usually an excellent prognosis, some patients experience disease recurrence or death. The aim of this study was to identify prognostic markers to stratify PTC patients. Patients and Methods Eight gene-expression profiles (GSE3467, GSE3678, GSE5364, GSE27155, GSE33630, GSE53157, GSE60542, and GSE104005) were obtained from the Gene Expression Omnibus and used to analyze diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Principal component analysis (PCA) was conducted to evaluate the separation of low- and high-risk THCA ( 17 ). To further validate the advantage and stability of the novel signature, the C-index of our signature and other three models was compared ( 18 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…Principal component analysis (PCA) was conducted to evaluate the separation of low- and high-risk THCA ( 17 ). To further validate the advantage and stability of the novel signature, the C-index of our signature and other three models was compared ( 18 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…Two different gene signatures including PTX3 were identified for the subtypes arising from the follicular cells: papillary, follicular and anaplastic. These new evidences suggest that the molecule could be an independent prognostic factor for most of the thyroid carcinomas ( 54 ), and a diagnostic tool to differentiate the anaplastic thyroid carcinoma from the other two subtypes ( 55 ).…”
Section: Discussionmentioning
confidence: 91%
“…A recent study identified a four genes signature including PTX3, 3′-phosphoadenosine 5′-phosphosulfate synthase 2 (PAPSS2), procollagen C-endopeptidase enhancer 2 (PCOLCE2) and transforming growth factor beta receptor 3 (TGFBR3) for papillary carcinoma as marker for risk stratification and survival prediction ( 54 ). PTX3 expression was significantly lower in patients surviving with tumors than in tumor free patients, revealing a potential correlation between PTX3 and tumor recurrence.…”
Section: The Link Between Ptx3 and Thyroid Diseasesmentioning
confidence: 99%
“…LINC01089 can block the malignant progression of TC by binding hsa-miR-27b-3p to increase the level of FBLN5 protein [ 31 ]. TGFBR3 expression is down-regulated in PTC tissues and is associated with OS of patients [ 32 ]. Herein, hsa_circ_0070100-hsa-miR-27a-3p/hsa-miR-27b-3p-TGFBR3 axis was identified.…”
Section: Discussionmentioning
confidence: 99%